Tanshinone IIA Inhibits Growth of Keratinocytes through Cell Cycle Arrest and Apoptosis: Underlying Treatment Mechanism of Psoriasis - Fu-Lun Li (Evidence-Based Complementary and Alternative Medicine, 2012)
The aim of the present investigation was to elucidate the cellular mechanisms whereby Tanshinone IIA (Tan IIA) leads to cell cycle arrest and apoptosis in vitro in keratinocytes, the target cells in psoriasis. Tan IIA inhibited proliferation of mouse keratinocytes in a dose- and time-dependent manner and induced apoptosis, resulting in S phase arrest accompanied by down-regulation of pCdk2 and cyclin A protein expression. Furthermore, Tan IIA-induced apoptosis and mitochondrial membrane potential changes were also further demonstrated by DNA fragmentation, single-cell gel electrophoresis assay (SCGE), and flow cytometry methods. Apoptosis was partially blocked by the caspase-3 inhibitor Ac-DEVD-CHO. Mitochondrial regulation of apoptosis further downstream was investigated, showing changes in the mitochondrial membrane potential, cytochrome c release into the cytoplasm, and enhanced activation of cleaved caspase-3 and Poly ADP-ribose polymerase (PARP). There was also no translocation of apoptosis-inducing factor (AIF) from mitochondria to the nucleus in apoptotic keratinocytes, indicating Tan IIA-induced apoptosis occurs mainly through the caspase pathway. Our findings provide the molecular mechanisms by which Tan IIA can be used to treat psoriasis and support the traditional use of Salvia miltiorrhiza Bungee (Labiatae) for psoriasis and related skin diseases.